Dieback and mortality of Nothofagus in Britain: ecology, pathogenicity and sporulation potential of the causal agent Phytophthora pseudosyringae. (26th May 2015) - Scanu, B.; Webber, J. F.
Abstract : Since 2009 extensive dieback and mortality of Nothofagus obliqua, associated with bleeding cankers on stems and branches, has been observed in the UK. The causal agent was identified as Phytophthora pseudosyringae, based on morphological and analysis of the internal transcribed spacer (ITS) sequences. Between 2011 and 2013, a survey assessed the frequency and nature of these P. pseudosyringae infections. Mature trees of Nothofagus with stem lesions caused by P. pseudosyringae were found across England, Scotland and Wales. Additional symptoms such as twig blight and leaf necrosis indicated that aerial infection was occurring. Besides N. obliqua, other hosts regularly encountered included Nothofagus alpina, Fagus sylvatica and Vaccinium myrtillus . In pathogenicity tests involving inoculation of logs, P. pseudosyringae was shown to be an aggressive bark pathogen of N. obliqua and F. sylvatica, but significantly less aggressive on N. alpina . Foliage susceptibility and sporulation tests showed marked differences between the six host species tested. Leaves of N. obliqua and V. myrtillus were highly susceptible. Leaves of N. alpina were moderately susceptible, those of Rhododendron ponticum slightly susceptible and those of F. sylvatica not susceptible at all. High levels of sporulation were observed only on inoculated N. obliqua and V. myrtillus leaves. This suggests that P. pseudosyringae may sporulate heavily on N. obliqua foliage in the field and that this inoculum initiates the aerial lesions observed on the shoots, branches and stems. The results also suggest that P. pseudosyringae has the potential to pose a serious threat to N. obliqua and other Nothofagus species in their Southern Hemisphere native ranges.